Higher-Order Thinking Skills (HOTS)-Based Learning in Islamic Religious Education - Miladisani Ammar Umah (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article discusses the importance of implementing Higher Order Thinking Skills (HOTS)-based learning evaluation in Islamic Religious Education (PAI) subjects. This topic is very crucial considering that PAI in the modern era is not sufficiently delivered through conventional methods such as memorization and lectures, but must encourage students to think critically, creatively, and reflectively towards religious teachings. The method used in this writing is a library research with a qualitative descriptive approach, reviewing relevant literature related to HOTS and its implementation in PAI learning evaluation. The results of the study indicate that HOTS-based evaluation is able to develop students' abilities in analyzing, evaluating, and creating solutions to contextual problems, thus supporting the formation of adaptive and highly reasoned religious characters. The implication is that the application of HOTS-based evaluation in PAI learning contributes significantly to students' cognitive development and is very relevant in the study of developmental psychology, especially in forming balanced intellectual and emotional intelligence.